2012
DOI: 10.1127/0003-5548/2011/0119
|View full text |Cite
|
Sign up to set email alerts
|

Variations of scalp, pubic and axillary hair

Abstract: Hair examinations and comparisons conducted by forensic scientists often provide investigative and associative information. Apart from its length and its natural color, hair displays a morphologic diversity both macroscopically and microscopically. Pseudogenization of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Hair diameter changes across the lifespan and varies between-individuals (Messenger, 2011; Mistry et al, 2012; Robbins, 2012). However, the evidence for a direct relationship of age and hair fiber diameter is mixed with regard to the type and direction of the relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Hair diameter changes across the lifespan and varies between-individuals (Messenger, 2011; Mistry et al, 2012; Robbins, 2012). However, the evidence for a direct relationship of age and hair fiber diameter is mixed with regard to the type and direction of the relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Hrdy opined that hair form was determined by multiple genes, and that tightly curly hair form had evolved convergently in African and Melanesian populations because of similar environmental pressures, but did not speculate on the possible functional significance of hair form. Since Hrdy's research, comparative studies of hair form have focused on forensic applications, not on phylogeny and function. The latter questions are being approached slowly, as variant genes associated with distinct hair phenotypes are identified.…”
Section: Evolution Of Human Scalp Hair Phenotypesmentioning
confidence: 99%
“…In this study, we examined the keratin expression in medullated human scalp hairs. We used Asian occipital hair which, besides being androgen‐insensitive, is more frequently medullated than in other ethnicities . We found that the medulla of occipital and sexual hairs exhibited essentially identical keratin patterns.…”
mentioning
confidence: 99%
“…Unlike most mammals, in man only androgen‐dependent sexual hairs, i.e. beard, pubic and axillary hairs, are regularly medullated, while the frequency of medullation in scalp hairs varies among individuals and ethnicities . Recently, we reported that out of the 54 human keratins, 12 epithelial keratins [comprising members of the outer and inner root sheath (ORS, IRS), the companion layer (cl), and the almost ubiquitously expressed keratin K80, as well as 12 hair cortex keratins] are present in the medulla of beard hairs .…”
mentioning
confidence: 99%
See 1 more Smart Citation